Sexual behaviour and incidence of HIV and sexually transmitted infections among men who have sex with men using daily and event-driven pre-exposure prophylaxis in AMPrEP: 2 year results from a demonstration study. Issue 7 (July 2019) - Hoornenborg, Elske; Coyer, Liza; Achterbergh, Roel C A; Matser, Amy; Schim van der Loeff, Maarten F; Boyd, Anders; van Duijnhoven, Yvonne T H P; Bruisten, Sylvia; Oostvogel, Paul; Davidovich, Udi; Hogewoning, Arjan; Prins, Maria; et al.
Summary: Background: Pre-exposure prophylaxis (PrEP) for HIV might induce risk compensation, defined as increased sexual risk behaviour leading to increased incidence of bacterial sexually transmitted infections (STIs). We examined the incidence of HIV, STIs, and sexual behaviour after initiating daily and event-driven PrEP. Methods: AMPrEP is a demonstration study that assessed the incidence of HIV and bacterial STIs and sexual behaviour among PrEP users at the STI clinic of the Public Health Service of Amsterdam (Amsterdam, the Netherlands). Eligible adults (aged ≥18 years) were HIV-negative men who have sex with men (MSM) and transgender people who had reported one or more of the following in the previous 6 months: condomless anal sex with casual partners, at least one bacterial STI, use of post-exposure prophylaxis after a sexual risk incident, or an HIV-positive sexual partner with detectable viral load. Participants were given a choice of daily PrEP or event-driven PrEP regimens. Participants were seen every 3 months for HIV and STI testing. Participants also completed self-administered questionnaires about sexual behaviour at each visit. Over the first 2 years, we assessed the number and incidence rate of HIV and chlamydia, gonorrhoea, and syphilis, including STIs diagnosed in between study visits and assessed changes in incidence over time using piecewise exponential survival models. The number of sexual acts and sexual partners were also analysed and changes over time were assessed using negative binomial regression models. This study is ongoing; the data cutoff for this analysis was June 30, 2018. Findings: Between Aug 3, 2015, and May 31, 2016, 376 participants were recruited, of whom nine participants were lost to follow-up, thus 367 participants were included in the analysis. Overall, 365 MSM and two transgender women were included, contributing 681·7 person-years of follow-up. At enrolment, 269 (73%) of 367 participants chose daily PrEP and 98 (27%) participants chose event-driven PrEP. Two individuals in the daily PrEP group became HIV-positive; overall HIV incidence rate was 0·30 per 100 person-years (95% CI 0·07–1·19). 253 participants were diagnosed with one or more STI during the first 2 years (incidence rate 90·4 per 100 person-years). STI incidence did not change over time (adjusted incidence rate ratio [aIRR] 1·00 per 3 month follow-up, 95% CI 0·93–1·07). More than a quarter of all STIs were diagnosed from tests done in between study visits. STI incidence was lower in the event-driven PrEP group than the daily PrEP group (aIRR 0·59, 95% CI 0·46–0·75). The number of condomless anal sex acts with casual partners per 3 months increased, but the number of partners and sex acts remained stable. Interpretation: Although the overall incidence of STIs did not change during 2 years of PrEP use, the incidence of STIs was higher among participants using daily PrEP than those using event-driven PrEP, which is likely a result of differences in sexual behaviour. This finding suggests the need to tailor STI prevention interventions according to behavioural profiles. Funding: ZonMw, H-TEAM, Internal GGD research funds, Aidsfonds, Stichting AmsterdamDiner Foundation, Gilead Sciences, Janssen Pharmaceutica, M A C AIDS Fund, and ViiV Healthcare.